Graphene hybridized polydopamine-kaolin composite as effective adsorbent for methylene blue removal. (15th March 2019) - He, Kai; Zeng, Guangming; Chen, Anwei; Huang, Zhenzhen; Peng, Min; Huang, Tiantian; Chen, Guiqiu
Abstract: To explore the approach for further enhancing the dye removal performance of polydopamine (PDA) coated materials, a novel composite of PDA-kaolin with reduced graphene oxide hybridization (PDA-rGO-kaolin) was synthesized and selected as a model adsorbent for methylene blue (MB) removal. The BET characteristic analysis showed that the introduction of rGO significantly increased the surface area of PDA-kaolin by 3.1 times. A series of comparative experiments on PDA-kaolin and PDA-rGO-kaolin towards MB removal in various conditions were carried out. Adsorption experiment indicated that PDA-rGO-kaolin was more satisfactory for MB removal. Kinetic analysis showed that the adsorption followed a pseudo-second-order kinetic model. The adsorption behavior could be better described by Langmuir isotherm model. Compared with PDA-kaolin, PDA-rGO-kaolin showed higher maximum adsorption capacity towards MB (39.663 mg/g). Furthermore, the adsorption of MB molecules on adsorbents was spontaneous and endothermic process according to thermodynamic experiment. Moreover, PDA-rGO-kaolin showed a good regeneration performance for MB removal. These results show that the introduction of graphene is a feasible and efficient method to improve the adsorption performance of PDA coated kaolin composite.